1997
DOI: 10.1093/aje/145.8.762
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Questionnaire Data and Medical Records of Chronic Diseases in Middle-aged and Elderly Finnish Men and Women

Abstract: The agreement between self-reported diseases in a questionnaire survey and data from medical records was assessed in a representative sample of Finnish men and women (n = 596) aged 45-73 years. The accumulated medical record information was abstracted from the records in the health centers and the central hospital in the study region. The agreement between the two information sources was substantial (kappa 0.73-0.80) for cardiovascular diseases as a group, hypertension, angina pectoris, myocardial infarction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
246
7
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(278 citation statements)
references
References 18 publications
17
246
7
8
Order By: Relevance
“…Thus, our results refer to individuals with diabetes diagnosed in early middle-age. The agreement between self-report and medical record diagnoses of diabetes is good [8], and our analyses using inpatient hospital discharge records were very similar to those for the main analyses using self-report. Self-report of adult weight and height may be biased, but the association between adult BMI and diabetes in this study, consistent with other studies using measured BMI, suggests that there is no major bias.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, our results refer to individuals with diabetes diagnosed in early middle-age. The agreement between self-report and medical record diagnoses of diabetes is good [8], and our analyses using inpatient hospital discharge records were very similar to those for the main analyses using self-report. Self-report of adult weight and height may be biased, but the association between adult BMI and diabetes in this study, consistent with other studies using measured BMI, suggests that there is no major bias.…”
Section: Discussionsupporting
confidence: 66%
“…39,40 Another limitation is that undiagnosed hypertension and other risk factors were not accounted for, since 6.4% of respondents admitted never having their BP measured. A major drawback to our study is the absence of any clinical measurement for the documentation of hypertension; however, several studies carried out both nationally 41 and internationally [42][43][44][45][46] to assess the validity of self-reported chronic diseases including hypertension revealed a moderate to substantial agreement between questionnaire data and either clinical examinations 42,43 or medical records. [44][45][46] A study carried out in Beirut 41 to assess the agreement between selfreported morbidity and physical examination, revealed that heart disease had the highest agreement followed by hypertension and concluded that the health interview survey was reasonably accurate for data collection of chronic conditions, which are clearly defined for the population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the validity of such self reports 22,23 have shown them to be relatively reliable. Such self reports would presumably cause only minor misclassification errors, which would only cause slight underestimates of the true impact of reverse causation due to smoking and serious illness.…”
Section: Discussionmentioning
confidence: 99%